An updated review of adipose derived-mesenchymal stem cells and their applications in musculoskeletal disorders. (4th March 2019) - Rivera-Izquierdo, Mario; Cabeza, Laura; Láinez-Ramos-Bossini, Antonio; Quesada, Raul; Perazzoli, Gloria; Alvarez, Pablo; Prados, Jose; Melguizo, Consolación
ABSTRACT: Introduction : Adipose-derived mesenchymal stem cells (ASCs) represent a new therapeutic strategy in biomedicine with many potential applications, especially in musculoskeletal disorders. Preclinical and clinical studies based on the administration of ASCs support their efficacy in bone regeneration, joint repair, tendon injury and skeletal muscle alterations. Many of these novel treatments may improve patients' quality of life and prognosis. However, several concerns about the use of stem cells remain unsolved, particularly regarding their safety and side effects. The present work aims to review the nature, clinical trials and patents involving the use of ASCs in musculoskeletal disorders. Area covered : In this article, we describe ASCs' isolation, culture and differentiation in vivo and in vitro, advances on ASCs' applications in bone, cartilage, muscle and tendon repair, and patents involving the use of ASCs. Expert opinion : The use of ASCs in musculoskeletal disorders presents significant therapeutic advantages, including limited autoimmune response, potential cell expansion ex vivo, high plasticity to differentiate into several mesodermal cell lineages, and additional effects of therapeutic interest such as secretion of neurotrophic factors and anti-inflammatory properties. For these reasons, ASCs are promising therapeutic agents for clinical applications in musculoskeletal disorders.